Reconstruction of large abdominal wall tissue defect using vacuum assisted wound closure - Ali, Sheikh; Khurram, Mohammed; Yaseen, Mohd (Journal of Surgery and Medicine, 2022)
Background/Aim: Abdominal wall defects may result from trauma, burn, necrotizing soft tissue infection or complications of abdominal surgeries. Reconstruction poses a great challenge for the surgeon in cases of large abdominal wall defects with lack of surrounding tissue. Abdominal wall defects lack a good functional and aesthetic impact and early reconstruction is prudent for better outcomes. This study evaluates the results of Vacuum assisted wound closure (VAC) therapy in patients with large anterior abdominal wall tissue defect which could not be closed primarily otherwise. Methods: This case series included 20 patients with partial thickness, anterior abdominal wall tissue defects. All patients had suffered an acute trauma. Wound debridement was done and VAC therapy dressing was applied in systematic manner. Dressing was changed every 3 or 4 days and continued up to 9-14 days. Results: Twenty patients underwent VAC therapy with an average age of 32 years (range, 25-52 years). Indications comprised tissue loss after acute trauma due to road traffic accident, burn and other trauma leading to anterior abdominal wall soft tissue defect. VAC was used for an average of 12 days, with an average negative pressure of 125 mm Hg. Healthy granulation tissue was formed in all patients. Subsequently split thickness skin grafts were applied in these patients. This results in early recovery as well as decreased morbidity in all patients. Conclusions: All patients had good tolerance to Vacuum-assisted closure. It offers many benefits comprising fewer dressing changes and an earlier return to daily activities. Patients with large abdominal defects can benefit from this procedure.